PERAN DAERAH ISTIMEWA YOGYAKARTA (DIY) DALAM MEMBANGUN POTENSI MARITIM NUSANTARA - Wegig Pratama (Majalah Ilmiah Bahari Jogja, 2016)
The purpose of this research is both to mapping various maritime potency that is available in Yogyakarta Special District Territory and as a priority program in maritime development issues through Human resource development toward Yogyakarta as a driving force in building the potency of maritime archipelago. This research accommodates the stakeholders thought in building maritime industry in Yogyakarta. Using empiric approach, policy decisionmaking and some literature brought up various acceleration programs in maritime industry as follows; first, proposing maritime issues in education curriculum from elementary school until high school so that it may return transformation of the maritime vision which now shifts to the land. Second, building new education institution and training program to fulfill the need of qualified human resources in maritime industry which is not yet fulfilled by the current institutions. The criteria is focused on the vocational education which is integrated with all maritime affairs, curriculum, equipment and tools and international-standard human resources to fulfill the need of both national and international human resources. Third, standardizing all the existing training equipment and tools based on international standard. Nowadays, both private and state maritime vocationalschoolsin Yogyakarta have not yet fulfilledthe required minimum standard. Fourth, conducting cooperation with foreign accredited education institutions and training programs which are best suited with education character in Yogyakarta. By this effort, It will increase the quality of the graduates students of the schools. Fifth, increasing the quality and quantity of human resources in maritime sector based on the society demands both through formal and informal training education. Sixth, improving research and development in maritime issues and building maritime laboratories to implement innovated technology and non-technology. Seventh, setting maritime community as a media to collaborate and evaluate the program. Eight, conducting cooperation with investors to build port and to supply 50 GT vessel onward to contribute giving better income for fishermen. Keywords: maritime potency, driving force, human resources, Yogyakarta